Analysis of strategies zakat, infaq, and alms collection at BAZNAS Semarang Regency - Farkhah Farkhah (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
Inhibitors of the Zakat collection in the BAZNAS Semarang Regency. This research uses descriptive qualitative research methods. The results showed that the strategy used to increase the collection of zakat, infaq, and sadaqah funds was through socialization, both directly and indirectly, and through pick-up service. The results of the SWOT analysis show that the Semarang Regency BAZNAS in carrying out the collection of zakat experiences several obstacles, but these obstacles can be overcome by the strength of the Semarang Regency BAZNAS. From several aspects caused by weakness, BAZNAS of Semarang Regency is still categorized as a stable position, considering that BAZNAS Semarang Regency is still able to implement programs and has tried to innovate to increase the collection of zakat, infaqs, and sadaqah in the future. The author recommends that the Semarang Regency BAZNAS pay more attention to intensive and continuous work program socialization, as well as enlightenment to the public about the primacy of ZIS payments through the BAZNAS that does not reduce virtue and reward, compared to being channeled directly to mustahik.